Analisis Perbandingan Regulasi dan Perlindungan Hukum atas Privasi Data Pasien di Tiga Negara Asia Tenggara (Indonesia, Singapura, dan Laos) - Heri Heriyanto (Jurnal Ners, 2023)
Legislation and legal protection of patient data privacy in e-health systems in Indonesia, Singapore, and Laos will be compared in this study. The present analysis highlights the strengths and weaknesses of the regulatory framework, identifies challenges, and suggests future directions to improve patient data privacy of patient. The findings reveal that while all three countries have established laws and regulatory bodies to address patient data privacy, Singapore stands out for its comprehensive and robust framework. Singapore's Personal Data Protection Act (PDPA), backed by effective enforcement measures, addresses several different data protection and privacy rights issues. While efforts have been made by Indonesia and Laos to regulate patient data privacy, there is still room for improvement, particularly in enforcement methods and compliance with international standards. Identified challenges include limited resources, awareness and compliance gaps, cybersecurity risks, and cross-border data sharing. Some directions for the future include strengthening enforcement mechanisms, increasing international collaboration to harmonize data protection standards, promoting data governance and accountability within healthcare organizations, increasing public awareness and empowering patients, and continuously evaluating and adapting regulatory frameworks to address evolving risks and technological advancements.